Technological Innovation and Industrial Upgrading in China’s Automotive Industry: The Dual Mechanisms of Global Value Chain Mediation and Industrial Agglomeration Moderation - Tingting, Sun; Muhammad Asraf, Abdullah (MDPI, 2025)
Amid global economic transformation, technological innovation is widely recognized as a pivotal driver for the sustainable upgrading of the automotive industry. This is particularly critical for China, the world’s largest automotive market, which faces persistent challenges, including technological bottlenecks in core components and confinement to low-value segments within global value chain. This study introduces novelty by systematically integrating and empirically testing the mediating role of Global Value Chain (GVC) and the moderating effect of industrial agglomeration within a unified framework—a focus that remains underexplored in the sector. Using panel data from 28 Chinese provinces (2000–2020), we measure industrial upgrading using the DEA-Malmquist index to capture total factor productivity changes and employ a system GMM approach. The results indicate that technological innovation directly fosters industrial upgrading and indirectly facilitates it by improving the industry’s GVC position. Moreover, industrial agglomeration positively moderates this relationship, thereby amplifying the returns to innovation within geographic clusters. These findings highlight the necessity for integrated policies that simultaneously promote technological innovation, strategic GVC positioning, and synergistic industrial agglomeration to achieve sustainable upgrading. As a paradigmatic emerging economy, China’s experience offers valuable insights for other latecomer economies pursuing industrial upgrading.